Wildflowers of the North Saskatchewan River Valley: making natural pigments for painting using rock minerals - Gonzalez-Escamilla, Carolina (My University, 2024)
This project of painting with rock minerals was initiated by an interest in caring for the environment, painting in a more environmentally friendly way, and learning how ancient cultures used to paint. The work on display showcases some of the native wildflowers that grow in the area of the North Saskatchewan River where the rocks were picked. Nature provided two elements for this composition: the rock pigments (material) and the native flowers of the North Saskatchewan River Valley (subject). The natural pigments for this painting were extracted from rocks by the process of pulverization. The rocks were ground by hand into fine powder, which was combined with a natural binder to make the paints. Carolina is a multidisciplinary artist originally from Mexico, currently living and creating in Treaty Six territory. She is in her first year of the Studio Arts program at MacEwan University. She works in painting, metals, photography, and digital art. She loves nature and everything outdoors. She received funding from the Student Undergraduate Research Fund from the Faculty of Fine Arts and Communications at MacEwan University for the purpose of developing this project.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: painting; natural pigments; North Saskatchewan River Valley